A bidirectional multiport DC‐DC converter applied for energy storage system with hybrid energy sources. (18th March 2021) - Pourjafar, Saeed; Shayeghi, Hossein; Sedaghati, Farzad; Seyedshenava, Seyedjalal; Blaabjerg, Frede
Summary: This paper presents a novel bidirectional multiport DC‐DC converter for the electrical vehicles with hybrid energy sources. The benefits of the suggested converter are high voltage conversion ratio and high efficiency, simple structure, low voltage stress across the semiconductor elements, low number of components, and common ground features. It has two bidirectional ports, which are suitable for energy storage systems (ESS) such as a battery. Due to the step‐up and step‐down operations of the proposed converter, it can charge and discharge the ESS. Additionally, only two power switches with low ON‐state resistance are utilized that make the control circuit to be simple. Furthermore, the suggested converter has low number of component, which leads to decrease its volume and cost. The operation principle in buck and boost mode is analyzed thoroughly. Finally, to verify the analysis and effectiveness of the proposed structure, a laboratory prototype is built with 12‐ and 20‐V input voltages and a power rating of 120 W used in 50‐kHz operating frequency. Abstract : This paper presents a novel bidirectional multiport DC‐DC converter for the electrical vehicles with hybrid energy sources. The benefits of the suggested converter are high voltage conversion ratio and high efficiency, simple structure, low voltage stress across the semiconductor elements, low number of components, and common ground features. It has two bidirectional ports, which are suitable for energy storage systems (ESS) such as a battery. Due to the step‐up and step‐down operation of the proposed converter, it can charge and discharge the ESS.